The Effects of Pollution Taxation on the Pattern of Resource Allocation: The Downstream Diffusion Case - Hochman, Eithan; Pines, David; Zilberman, David (Quarterly Journal of Economics, 1977)
I. Introduction, 625.—II. Model I—the case of positive social costs of pollution at the urban center when natural absorption exists, 627.—III. Model II—the case of pollution externality in production, 633.—IV. Concluding remarks: integration of the two models, 637.